PERAN DINAS PENDAPATAN DAERAH KOTA BATU DALAM UPAYA PENINGKATAN PAJAK HIBURAN - Wijaya, Ahmad Ardy (Jurnal Mahasiswa Perpajakan, 2015)
Regional autonomy gives freedom to local government to arrange their own territory, which it is related to the financing of local governments through tax revenue. In the process local government gives the authorize of entertainment tax revenue to Local Revenue Offices to levy entertainment tax revenue. The purpose of this research is to know the role from Local Revenue Offices of Batu, East Java in the effort to in terms of entertainment tax increase in extensification and intensification. Local Revenue Offices of Batu, East Java is improve the entertainment tax revenue through intensification and extensification entertainment tax on voting generally runs well though with some of the obstacles in the process of voting. This research used descriptive research methods with qualitative approaches. Keywords: Department of Revenue, Batu city, Entertainment Tax, extensification and intensification Abstrak Otonomi daerah memberikan kebebasan kepada pemerintah daerah untuk mengatur daerahnya, salah satunya berkaitan dengan pembiayaan pemerintah daerah melalui penerimaan pajak hiburan. Dalam proses penerimaan pajak hiburan pemerintah daerah memberikan kewenangan kepada Dinas Pendapatan Daerah untuk memungut hasil penerimaan pajak hiburan. Tujuan penelitian ini adalah untuk mengetahui peran Dinas Pendapatan Daerah Kota Batu dalam upaya peningkatan pajak hiburan dari segi ekstensifikasi dan intensifikasi. Upaya yang dilakukan Dinas Pendapatan Kota Batu dalam rangka meningkatkan penerimaan pajak hiburan melalui intensifikasi dan ekstensifikasi pemungutan pajak hiburan pada umumnya berjalan dengan baik meski dengan beberapa hambatan dalam proses pemungutan. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kualitatif. Kata Kunci: Peran, Dinas Pendapatan Daerah, Kota Batu, Pajak Hiburan, ekstensifikasi dan intensifikasi